Targeting dendritic cells in pancreatic ductal adenocarcinoma - Deicher, Anton (Cancer Cell Int, 2018)
Dendritic cells (DC) are an integral part of the tumor microenvironment. Pancreatic cancer is characterized by reduced number and function of DCs, which impacts antigen presentation and contributes to immune tolerance. Recent data suggest that exosomes can mediate communication between pancreatic cancer cells and DCs. Furthermore, levels of DCs may serve as prognostic factors. There is also growing evidence for the effectiveness of vaccination with DCs pulsed with tumor antigens to initiate adaptive cytolytic immune responses via T cells. Most experience with DC-based vaccination has been gathered for MUC1 and WT1 antigens, where clinical studies in advanced pancreatic cancer have provided encouraging results. In this review, we highlight the role of DC in the course, prognosis and treatment of pancreatic cancer.